Creating Access for students with a disability in Pre-Service Education - Nonis, Karen (2023)
As school systems evolve with increased commitment towards inclusion and diversity in response to the changing demographics, access to educational platforms has increased over time. This change creating least restrictive environments both physical and virtual over time has flowed to the university. Policies both local and international have provided the clear guide and foundation to supporting inclusion and access in any educational setting. However, the challenges continue to permeate some countries still exploring these possibilities of inclusion and access for all students. This paper explores the challenges reported in studies that have responded to the needs of students given the changes in the policy. The author discusses such challenges while offering solutions to what could culminate into a stressful situation if access is not addressed. Examples are drawn from research data both locally and internationally.